Gustatory Dysfunction and Decreased Number of Fungiform Taste Buds in Patients With Chronic Otitis Media With Cholesteatoma. (September 2016) - Saito, Takehisa; Ito, Tetsufumi; Ito, Yumi; Yamada, Takechiyo; Okamoto, Masayuki; Manabe, Yasuhiro
Objective: To compare the number of fungiform taste buds among patients with chronic otitis media (COM), those with pars flaccida retraction type cholesteatoma, and those with pars tensa retraction type cholesteatoma in combination with gustatory function. Methods: Thirty-seven patients with COM, 22 patients with pars flaccida retraction type cholesteatoma, and 17 patients with pars tensa retraction type cholesteatoma were included. An average of 10 fungiform papillae (FP) per patient in the midlateral region of the tongue were observed by confocal laser scanning microscopy in vivo, and the average number of taste buds were counted. Just before the observation of FP, electrogustometry (EGM) was performed to evaluate gustatory function. Results: A significant decrease of the average number of fungiform taste buds and significant elevation of EGM thresholds were clarified in the pars tensa retraction type cholesteatoma group but not in the COM or pars flaccida type cholesteatoma group. Conclusion: It was suggested that some neurotoxic cytokines produced by cholesteatoma tissue might affect the CTN morphology, resulting in a decreased number of fungiform taste buds and elevation of EGM threshold in patients with pars tensa retraction type cholesteatoma.